Post-transplantation Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography in Patients with Lymphoblastic Lymphoma is an Independent Prognostic Factor with an Impact on Progression-Free Survival but not Overall Survival - Na Dai MD (SAGE Publishing, 2021)
Purpose: In the present study, we mainly aimed to evaluate the prognostic value of 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]F-FDG) positron emission tomography (PET)/computed tomography (CT) after allogeneic stem cell transplantation (allo-SCT) in lymphoblastic lymphoma (LBL) patients using Deauville Scores (DS). Materials and Methods: A total of 63 LBL patients who benefited from 18 F-FDG PET-CT after allo-SCT in our institution between April 2010 and August 2020 were enrolled in this retrospective study. These above-mentioned patients were divided into two groups based on the Deauville criteria. Diagnostic efficiency of 18 F-FDG PET/CT and integrated CT in detecting lymphoma were calculated. Consistencies were evaluated by comparing 18F-FDG PET/CT and integrated CT results through kappa coefficient. Kaplan-Meier method was used in survival analysis, and the log-rank method was adopted in comparisons. Prognostic factor analysis was performed by the Cox regression model. Results: The sensitivity, specificity, positive predictive value, negative predictive value, accuracy of post-SCT 18 F-FDG PET-CT were 100%(12/12), 92.2%(47/51), 75.0%(12/16), 100%(47/47) and 93.7%(59/63). The consistency of 18F-FDG PET-CT and integrated CT was moderate(Kappa = .702，P < .001). Positive post-SCT 18F-FDG PET-CT was associated with lower progression-free survival (PFS) but not overall survival (OS) (p = .000 and p = .056, respectively). The 3-year PFS of the PET-positive group and PET-negative group was 18.8% and 70.2%, respectively. Multivariate analysis showed that post-SCT PET-CT findings was an independent prognostic factor for PFS (p = .000; HR, 3.957; 95%CI, 1.839-8.514). Other factors independently affecting PFS were sex (p = .018; HR, 2.588; 95% CI, 1.181 − 5.670) and lactate dehydrogenase (LDH) (p = .005; HR, 3.246; 95% CI, 1.419 − 7.426). However, none of the above-mentioned factors were associated with OS. Conclusions: Collectively, we found that 18F-FDG PET-CT after allo-SCT was a strong indicator for PFS, but not OS, which might provide important evidence for the selection of subsequent treatment regimen for LBL patients. Trial registration number: ChiCTR2100046709.